Range grazing capacity raised: Program of seeding annual clovers, fertilization and grazing management resulted in improved forage quality and quantity - W Williams; R Merton Love; J Conrad (California Agriculture, 1956)
A threefold increase in grazing capacity was achieved in a five-year range improvement program involving the seeding of adapted clovers, phosphorus fertilization, and grazing management on over 500 acres. Grazing records and quadrat harvests demonstrate the marked success of the improvement methods.